2010
DOI: 10.1160/th10-01-0069
|View full text |Cite
|
Sign up to set email alerts
|

Circulating monocyte subsets and cardio - vascular risk factors in coronary artery disease

Abstract: The aim of our study was to evaluate possible associations of circulating monocyte subsets with cardiovascular risk and the extent of coronary artery disease (CAD). Monocytes in peripheral blood have been divided into functional subsets on the basis of their expression of the lipopolysaccharide receptor CD14 and the Fc-γ receptor CD16 (1-4). CD14 ++ CD16cells represent the major monocyte population, highly express CCR2 and are often described as "classical" monocytes. The tissue macrophage-like CD14 + CD16 + s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 12 publications
3
38
0
2
Order By: Relevance
“…At baseline, cell counts of all 3 monocyte subsets were correlated with traditional as well as nontraditional cardiovascular risk factors. Interestingly, CD14ϩϩCD16ϩ monocytes seem particularly to integrate cardiovascular risk burden, a notion that is supported by earlier data (26). Of most interest, CD14ϩϩCD16ϩ monocytes were the only independent predictors of adverse cardiovascular outcomes after full adjustment for traditional and nontraditional cardiovascular risk factors in the HOM SWEET HOMe study.…”
Section: C-statistics Corresponding To the Cox Regression Analyses Resupporting
confidence: 56%
“…At baseline, cell counts of all 3 monocyte subsets were correlated with traditional as well as nontraditional cardiovascular risk factors. Interestingly, CD14ϩϩCD16ϩ monocytes seem particularly to integrate cardiovascular risk burden, a notion that is supported by earlier data (26). Of most interest, CD14ϩϩCD16ϩ monocytes were the only independent predictors of adverse cardiovascular outcomes after full adjustment for traditional and nontraditional cardiovascular risk factors in the HOM SWEET HOMe study.…”
Section: C-statistics Corresponding To the Cox Regression Analyses Resupporting
confidence: 56%
“…17 In patients with stable coronary artery disease, the percentage of CD14 ϩϩ CD16 Ϫ monocytes was elevated in patients with 5 or more risk factors compared with low-to medium-risk patients. 18 Here we show that monocyte subsets measured at baseline can predict incident CVD, also, in a randomly selected population cohort over a median follow-up of 15 years. We also investigate if monocyte subsets are associated with extent of atherosclerosis at baseline by correlating monocyte subsets to intima media thickness in the carotid artery measured by ultrasound.…”
Section: Ccr2mentioning
confidence: 68%
“…The accumulation of such cells in peripheral blood mainly functioned in inducing and perpetuating the inflammatory process in patients with acute and chronic inflammatory diseases. Some studies [29][30][31] have shown that CD16 + monocyte counts are elevated in many inflammatory conditions and that CD16 + monocytes are efficient producers of inflammatory cytokines with high endothelial affinity.…”
Section: Discussionmentioning
confidence: 99%